Analysis of Factors and Issues Affecting the Brand Development of Lu Xun Academy of Fine Arts - Ming, Liu; Vanitwatthananuwat, Chaiyot (Journal of Cultural Analysis and Social Change, 2025)
The objectives of this research are (1) to study and analyze the current brand management of Lu Xun Academy of Fine Arts Art Museum, and (2) to analyze the factors affecting the brand effectiveness of Lu Xun Academy of Fine Arts Art Museum. This study employs qualitative methods to review effective brand management models for art museums through a literature review and to optimize these models based on the characteristics of the Lu Xun Academy of Fine Arts Art Museum. In addition, SWOT analysis is used to examine the internal and external factors and conditions of the target case and to infer the factors that influence brand performance. The research found that: (1) Lu Xun Academy of Fine Arts Art Museum adheres to the principle of supporting service, education as a venue for higher education research. Due to its relatively closed environment and small number of visitors, the Lu Xun Academy of Fine Arts Art Museum lacks the attention of society and the public. In addition, competition between art exhibition venues and museums is intense. The Lu Xun Academy of Fine Arts Art Museum recognizes the challenge of maintaining a strong market position. It therefore conducts research on brand development and identity enhancement through targeted approaches to development and marketing management. (2) The factors and problems of Lu Xun Academy of Fine Arts Art Museum that can improve brand efficiency are based on the museum's brand management system in four dimensions: quality and academic dimension, personal dimension, symbolic dimension, and organizational dimension, to develop and improve the brand efficiency of the university's art museum, aiming at effectively building its competitiveness and satisfying visitors.